The Effect of Organizational Climate and Servant Leadership on Job Satisfaction and Their Impacts on Employees’ Performance in The Midst Of Covid-19 Pandemic - Ari Apriani; Cristina Catur Widayanti; Magito Magito; Shafwan Shafwan (Journal of Management and Business Innovations, 2021)
During the Covid-19 pandemic, the Liaison Bureau of Lampung Province in Jakarta implemented WFH for some employees rotating due to the reduced number of people in the workspace. Of course, this will make the organizational climate not controlled directly, and employees need servant leadership to achieve their performance correctly. It influences the effectiveness and performance of the corporation's goal corporation withinside the future. The overall populace Liaison Bureau of Lampung Province in Jakarta turned 124 people. The estimation version used saturated sampling, so the variety of samples used on this look turned into seventy-four respondents (Civil Servants). Quantitative evaluation techniques have been utilized using SEM analysis software and SmartPLS. The impacts demonstrated that organizational climate had a positive and insignificant influence on job satisfaction, servant leadership had a positive and significant on job satisfaction, the organizational climate had a positive and significant on employee performance, servant leadership had a negative and significant on employee performance, job satisfaction had a positive and significant on employee performance, job satisfaction can mediate the influence of organizational climate on employee performance had a positive and significant, and job satisfaction is not able to mediate the influence of servant leadership on employee performance.Keywords: Employee performance, job satisfaction, organizational climate, servant leadership